Formulation of Film Soap Ethanol Extract Mesocarp of Red Watermelon (Citrullus lanatus) and Antioxidant Activity Test - Noni Rahayu Putri; Tisa Mandala Sari; Rizki Aulia Wulandari (Universitas Islam Negeri Alauddin Makassar, 2021)
Film soap is soap in the form of a thin layer having a thickness of 100 - 500 µm made of foaming film and plasticizer. The advantages of paper soap preparations are convenient in use, hygienic, practical, and easy to carry anywhere. Mesocarp red watermelon is a part of watermelon that contains flavonoid compounds that have antioxidant activity. The purpose of this study was to formulate the film soap of red watermelon mesocarp extract and to determine its antioxidant activity. In this study, the formulation was carried out by making four formulas with varying concentrations of ethanol extract mesocarp of red watermelon F0 = 0%; F1 = 1.5%; F2 = 2% and F3 = 3%. The evaluation was carried out in the form of organoleptic examination, pH, foam power, weight uniformity, moisture content, thickness, irritation test, stability and antioxidant activity tests. The evaluation results of the film soap from the four formulas were pH 9.29 - 9.12; weight uniformity 0.125 - 0.134 grams, water content 16.80 - 16.30%; thickness 0.14 - 0.15 mm and physically stable. The antioxidant activity of each formula was seen from the value, namely IC50F0 = 76.42µg / mL; F1 = 70.36 µg / mL; F2 = 65.14µg / mL; F3 = 62.14 µg / mL. From the research results, it can be concluded that the ethanol extract of red watermelon mesocarp can be formulated into film soap and has antioxidant activity which is included in the strong group.